Business Journalism How to Report on Business and Economics - Hayes, Keith; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Business Journalism: How to Report on Business and Economics is a basic guide for journalists working in countries moving to open-market economies, students in journalism courses, journalists changing direction from general news reporting to business and economic reporting, and bloggers. It also explains the differences in technique required for general reporters to deliver business news for text, TV, or radio. Veteran journalist Keith Hayes, who has worked for such organizations as Reuters, PBS, the BBC, CBC, and CNBC, provides a quick reference to journalistic practice that covers everything from how to meet a deadline to getting answers from company or government officials who would rather not talk. It also provides background on specific knowledge that journalists should have to report on the business and the economy accurately and with insight. That includes understanding the major markets and how they work, learning to read a balance sheet, and getting the story even when a company or government sets up roadblocks. As Hayes demonstrates, effective journalists are story tellers who need to tell the story well while making certain they are providing the facts as they find them and understand them. Among other things, readers will also learn: How to write a business news story How to report business news on television How to report in a globalized business world How to get usable information from press conferences and briefings The basics of macroeconomics, the financial markets, and company-specific financial data How to dig for facts and get the story This book covers comprehensively the basics of business and economic reporting. With its insights and tips from Hayes and other veteran journalists, it’s a book that will remain on your shelf for years to come and help you acquire and cement career-enhancing skills. It will also help you hone your craft as you begin to write more sophisticated stories and take jobs of increasing responsibility.
Keywords: Business; Management science; Business and Management, general